Bilateral Simultaneous Endoscopic Dacryocystorhinostomy: Outcome and Impact on the Quality of Life of the Patients - Herzallah, Islam R.; Marglani, Osama A.; Alherabi, Ameen Z.; Faraj, Nuha S.; Bukhari, Deemah H. (International Archives of Otorhinolaryngology, 2019)
Introduction Bilateral simultaneous endoscopic dacryocystorhinostomy (endo-DCR) has received little attention in the literature, thus many surgeons continue to address bilateral nasolacrimal duct obstruction at two stages, rather than in the same setting.Objective To evaluate the feasibility and the outcome of simultaneous bilateral Endo-DCR and its impact on the quality of life of the patients.Methods We have conducted a retrospective analysis of patients who underwent bilateral simultaneous endo-DCR between March 2013 and February 2017 at our tertiary care institution. The reviewed data included clinical presentation; operative details; success rate; pre and postoperative evaluation of the symptoms of the patients, using the Nasolacrimal Duct Obstruction Symptom Score Questionnaire; satisfaction of the patients, and improvement in the quality of life, assessed by the Glasgow Benefit Inventory (GBI) questionnaire.Results Out of 128 cases in which endo-DCRs were performed, 13 were bilateral (26 sides). Postoperative success was documented in 24 of the 26 sides (92.3%), with a mean follow-up duration of 16.2 months. The two failed sides were reported in the same case. The preoperative symptom score ranged between 12 and 80 (mean ± standard deviation [SD]: 38.23 ± 15.7). The postoperative symptom score was significantly lower (mean ± SD: 5.4 ± 12.9). The success rates in unilateral and bilateral cases were comparable, with no statistically significant difference. A notable improvement in the quality of life of the patients was also reported, with a mean GBI score of 81.38 ± 12.37.Conclusion Our results support that a simultaneous bilateral endo-DCR is a safe procedure that offers a high success rate, spares the patient from the stress of a second surgery, provides the patient with a bilateral resolution of the symptoms, and confers an immediate improvement in the quality of life of the patients.
Keywords: dacryocystorhinostomy; epiphora; dacryocystitis; nasolacrimal duct; lacrimal sac; quality of life; endoscopic DCR